Shifting to climate change aware cities to facilitate the city resilience implementation. (June 2020) - Iturriza, Marta; Labaka, Leire; Hernantes, Josune; Abdelgawad, Ahmed
Abstract: Climate change (CC) is one of the most urgent threats to modern societies, having direct and indirect consequences on the rapid growth of urban areas. Cities are attempting to both reduce their impact on the environment and build resilience to be able to face the irreversible effects of CC through plans and strategies. However, barriers, such as the fact that cities are complex systems and the uncertainty posed by CC have led to less engaged and committed city stakeholders, which have hampered the operationalisation of city resilience. In this context, developing city stakeholders awareness has been demonstrated to be an effective way to put an end to passive behaviour and help transform cities so they are more climate-resilient. Thus, we posit that developing city stakeholder awareness leads to more effective implementation of CC resilience-building plans. To that end, this paper presents a framework that defines the awareness-development process and combines it with an educational simulation tool that facilitates understanding of the theory presented in the framework. Finally, the paper presents a pilot test in the city of Kristiansand, Norway, to show the contribution of the simulation tool in improving city stakeholder awareness. Highlights: Stakeholders' awareness to climate change is key to operationalise city resilience. Developing awareness is a dynamic process where all city stakeholders take part. Developing awareness to climate change boosts stakeholders' proactivity. A simulation tool contributes to the understanding of a theoretical result.